An insight on electrospun-nanofibers-inspired modern drug delivery system in the treatment of deadly cancers. Issue 71 (2nd August 2015) - Balaji, A.; Vellayappan, M. V.; John, A. A.; Subramanian, A. P.; Jaganathan, S. K.; Supriyanto, Eko; Razak, S. I. A.
<x xml:space="preserve">Abstract</x> This review gives an insight into the process of electrospinning, its essential parameters, the types of drug incorporation and the works reported on common dreadful cancers.